City in all directions; an anthology of modern poems. - Adoff, Arnold; Carrick, Donald ([New York] Macmillan, 1969)
An anthology of poems celebrating city life around the world.
Keywords: Children's poetry; City and town life -- Poetry; Poetry -- Collections